Answer:
The answer to your question is y = 4/6x - 4
Step-by-step explanation:
Data
m = 4/6
P (0, -4)
slope-intercept form = ? y = mx + b where m is the slope and
b is the y-intercept
Formula
y - y1 = m(x - x1)
Substitution
y - (-4) = 4/6(x - 0)
Simplification
y + 4 = 4/6x
Result
y = 4/6x - 4
slope = 4/6 y-intercept = -4
<span>potential; kinetic is the answer.</span>
And soon it'll avenue golden retriever to play with.
God, i feel so stupid writing that :(
Answer:
5
Step-by-step explanation:
Kendall needs to lay off of the cookies lol
Answer:
d
Step-by-step explanation: